The impact of structural capital on the firm Innovativeness, the Galician Northern Portugal automotive industries reality - Helena Santos-Rodrigues; Pedro Figueroa; Carlos Maria Jardon (European Regional Science Association (ERSA), 2011)
The intellectual capital is increasingly considered a major issue on the management and organization research and a source of competitive advantage. Although there are different models and approaches that try to identify the effect of intellectual capital on firm performance, there's, also a lack of evidence and consensus. Based on that evidence, this paper focuses on the influence of the structural capital on the product- process and management innovativeness of the firm. A global model including the variables used in the previous literature is used and we establishes hypotheses for testing this model and use statistic technique to estimate the parameters of the model in a sample. To do so, we use a survey from 68 firms working on the auto components sector, established in the Northern Spain and Northern Portugal. We found firstly, that innovativeness has two main dimensions, perfectly differentiated, the product-process innovation and the management innovation; secondly that the structural capital dimensions influences differently each type of innovation capacity (innovativeness). We also concluded that the structural capital of the automotive firms based on the euro region Galicia (Spain) Northern Portugal influences positive and directly the management innovativeness. These results highlight the importance of the structural capital as well as highlight the main dimensions that influence the innovativeness, and more broadly, the value of intellectual capital as a competitive advantage in contemporary time. Moreover, point out the different character of product-process and management innovativeness.
Keywords: 330